Multiscale heterogeneous numerical simulation of asphalt mixture. Issue 3 (20th February 2019) - El Sawda, Christina; Fakhari‐Tehrani, Fateh; Absi, Joseph; Allou, Fatima; Petit, Christophe
Abstract: A multiscale heterogeneous numerical finite element (FE) model is a method used in order to prognosticate the asphalt mixture's mechanical behaviour at various scales (bitumen and mortar mastic). Thus, the aim of this research paper is to evaluate its accuracy. A biphasic approach was adopted to model the bituminous composite. The latter is made of elastic aggregates and viscoelastic matrix. In this developed multiscale method, the biphasic composite's properties are shifted from an initial scale to a greater one. The parameters inputted into the FE model consisted of the dynamic modulus and the elastic properties of the matrix at several scales. A software developed in our laboratory was used to obtain randomly generated aggregates. These inclusions have different sizes and shapes. Therefore, this program generates the bituminous composites' aggregate skeletons. Values of the complex modulus and phase angle obtained from numerical simulations were compared with those obtained by an analytical method based on the Generalized Self Consistent Scheme (GSCS) model and to experimental ones. The results confirm the accuracy of the global mechanical behaviour obtained from the generated heterogeneous numerical model. Lastly, at local scale, the asphalt mixture's mechanical behaviour was examined regarding the influence of the heterogeneous microstructures.